Dental educators’ perceptions, experience and understanding of reflective learning in dental education - Howell, Yvonne (Trinity College (Dublin, Ireland). School of Education, 2021)
Reflection and reflective practice in undergraduate education has gained increased prominence in health education in recent years. In an Irish context, we know little of how dental educators understand and perceive the purpose of reflective learning and how they facilitate its practice. The development of reflective practitioners is fundamental in dental education. The aim of this study is to explore dental educators’ understanding of and experience in reflective learning in the dental undergraduate curriculum. Literature review: An extensive review of literature was conducted covering: reflective practice in dental education, reflective learning theorists, teaching and assessment strategies and implications for dental educators. Methodologies: The study was carried out using qualitative methodology. It employed a one-method approach using semi-structured interviews. Participants were seven dental educators from undergraduate dental health programmes. After transcription, interview data was analysed thematically following the procedures of Braun and Clarke’s approach to Thematic Analysis. Findings: Although the educators agreed that reflective learning plays an important role within the dental undergraduate curriculum, the study identified that dental educators lack understanding of and experience in facilitating the reflective process. The study indicated the need and importance of having prior experience and support when facilitating reflective learning. The interviewees alluded to reviewing the curriculums regarding teaching and implementing reflective learning. They highlighted that reflection and reflective practice is given very little attention in the dental undergraduate curriculums. The findings further highlighted the importance of educators’ preparation and suggested the need for greater support from educational leaders. Conclusion and Recommendations: Dental educators need prior preparation to facilitate the reflective learning process with their students. Education on reflective learning should be provided for the entire faculty. There should be greater support and emphasis on the importance of reflective learning in all dental undergraduate curriculums. Reflective practice should be logically structured and standardised within the entire dental undergraduate curriculum.
Keywords: Higher Education; Education